Implementation of Trend Moment Method for Goods Stock Control - Imam Turmuzdi; Alif Catur Murti (Jurnal Transformatika, 2019)
Makin jaya shop is one of the shop that engaged in selling cloth and equipment  of school. But currently still using manual method in transactions and management of the data. So it need a system to efficien all of the performance by controllong stock items by forecasting  stocks that must be met. The trend moment method is able to forecast to estimate the amount of stock that must be met. The implementation of Trend Moment method on application  can predict for uniform white shirt items sales in the month and year desired by users by using two-year data on the Trend Moment method even though the maximum level of accuracy is 85.18%. The long term impact of the use of forecasting for goods stock control can increase sales profits and trust of customers.